On the public provision of positional goods - Désirée I. Christofzik; Sebastian Kessing (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2023)
We investigate whether public provision of positional goods can be a sensible instrument to address inefficiencies arising from relative-standing externalities associated with the excessive consumption of such goods. In situations where consumers face a discrete choice between a private and a public alternative, providing the latter for free or at a subsidized rate generates incentives to opt for the public alternative. This allows to reduce excessive consumption. We show that such policies can increase welfare and characterize situations where they can even implement efficiency. Efficiency can typically be achieved if the non-positional utility component is sufficiently important. Moreover, we investigate how public provision of positional goods may be a useful policy instrument in second-best situations, where either the government is constrained to rely on distortionary taxes, or where it redistributes facing information constraints.
Keywords: H42; D62; H52; 330; Positional goods; relative standing externality; publicly provided goods; in-kind provision